Bound by Borders: Voter Mobilization through Social Networks - Gary W. Cox; Jon H. Fiva; Max-Emil M. King (Center for Economic Studies and ifo Institute (CESifo), 2023)
A vast and growing quantitative literature considers how social networks shape political mobilization but the degree to which turnout decisions are strategic remains ambiguous. Unlike previous studies, we establish personal links between voters and candidates and exploit discontinuous incentives to mobilize across district boundaries to estimate causal effects. Considering three types of network—families, co-workers, and immigrant communities—we show that a group member's candidacy acts as a mobilizational impulse that propagates through the group's network. In family networks, some of this impulse is non-strategic, surviving past district boundaries. However, the bulk of family mobilization is bound by the candidate's district boundary, as is the entirety of the mobilizational effects in the other networks.
Keywords: D72; D85; C33; 330; political participation; social networks; electoral geography